2018
DOI: 10.1038/s41598-018-30477-8
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic map navigation in a migratory songbird requires trigeminal input

Abstract: Recently, virtual magnetic displacement experiments have shown that magnetic cues are indeed important for determining position in migratory birds; but which sensory system(s) do they use to detect the magnetic map cues? Here, we show that Eurasian reed warblers need trigeminal input to detect that they have been virtually magnetically displaced. Birds with bilaterally ablated ophthalmic branches of the trigeminal nerves were not able to re-orient towards their conspecific breeding grounds after a virtual magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 33 publications
4
47
0
1
Order By: Relevance
“…1a for scenarios 2−4). This would be in general agreement with the result from birds tested in Emlen funnels (Chernetsov et al 2008;Kishkinev et al 2013Kishkinev et al , 2015Pakhomov et al 2018) and/or with the real movements of displaced Common Cuckoos (Cuculus canorus) according to Willemoes et al's (2015) satellite tracking study. If the olfactory system plays a necessary role in true navigation, we predicted that birds without a functional sense of smell would not be able to determine their new location and either show disorientation (departure in random directions) or fall back to the normal migratory direction, as has been seen in other studies (Holland et al 2009;Wikelski et al 2015), whereas the control group would adjust to the displacement by shifting their orientation anti-clockwise, as mentioned above.…”
supporting
confidence: 88%
See 4 more Smart Citations
“…1a for scenarios 2−4). This would be in general agreement with the result from birds tested in Emlen funnels (Chernetsov et al 2008;Kishkinev et al 2013Kishkinev et al , 2015Pakhomov et al 2018) and/or with the real movements of displaced Common Cuckoos (Cuculus canorus) according to Willemoes et al's (2015) satellite tracking study. If the olfactory system plays a necessary role in true navigation, we predicted that birds without a functional sense of smell would not be able to determine their new location and either show disorientation (departure in random directions) or fall back to the normal migratory direction, as has been seen in other studies (Holland et al 2009;Wikelski et al 2015), whereas the control group would adjust to the displacement by shifting their orientation anti-clockwise, as mentioned above.…”
supporting
confidence: 88%
“…A further displacement experiment from the Courish Spit to Moscow demonstrated that an intact trigeminal nerve is necessary for the compensatory response shown by Reed Warblers (Kishkinev et al 2013). Following on from this, exposure to a changed magnetic field alone at the capture site simulating the displacement site in Zvenigorod elicited a compensatory goal-ward anti-clockwise re-orientation similar to the one documented after a real geographic displacement (Kishkinev et al 2015), and these compensatory responses also required intact trigeminal nerves (Pakhomov et al 2018). Another experiment at this capture site in which only declination was changed to match a location in Scotland showed that this magnetic parameter appears to be used to calculate longitudinal position, at least in Western Europe (Chernetsov et al 2017).…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations